Clinical Assessment of Lamina Cribrosa Curvature in Eyes with Primary Open-Angle Glaucoma - Kim, Yong Woo (PLoS One, 2016)
PURPOSE: Quantitative evaluation of lamina cribrosa (LC) posterior bowing in primary open-angle glaucoma (POAG) eyes using swept-source optical coherence tomography. METHODS: Patients with POAG (n = 123 eyes) and healthy individuals of a similar age (n = 92 eyes) were prospectively recruited. Anterior laminar insertion depth (ALID) was defined as the vertical distance between the anterior laminar insertion and a reference plane connecting the Bruch’s membrane openings (BMO). The mean LC depth (mLCD) was approximated by dividing the area enclosed by the anterior LC, the BMO reference plane, and the two vertical lines for ALID measurement by the length between those two vertical lines. The LC curvature index was defined as the difference between the mLCD and the ALID. The factors influencing the LC curvature index were evaluated. RESULTS: The ALID and mLCD were significantly larger in POAG eyes than in healthy controls (P < 0.05). The LC curvature index was significantly larger in POAG eyes than in healthy controls on both the horizontal (85.8 ± 34.1 vs. 68.2 ± 32.3 μm) and vertical meridians (49.8 ± 38.5 vs. 32.2 ± 31.1 μm, all P < 0.001). Multivariate regression showed significant associations of greater disc area (P < 0.001), vertical C/D ratio (P < 0.001) and mLCD (P < 0.001), smaller rim area (P = 0.001), thinner average RNFLT (P < 0.001), and myopic refraction (P = 0.049) with increased LC curvature index. There was no difference in the LC curvature index between mild (MD > –6 dB) and moderate-to-advanced glaucoma (MD < –6 dB, P = 0.95). CONCLUSIONS: LC posterior bowing was increased in POAG eyes, and was significantly associated with structural optic nerve head (ONH) changes but not with functional glaucoma severity. Quantitative evaluation of LC curvature can facilitate assessment of glaucomatous ONH change.